Does Government Spending, Investment, and Natural Resources Reduce Unemployment in Riau Province, Indonesia? - Hidayat, Muhammad; Armel, Raja Septian; Muslim, Resti Yulistia (International Journal of Economics and Financial Issues, 2025)
Unemployment is a major macroeconomic problem included in the SDG 2030 agenda, Goal 8. This study aims to analyze the unemployment rate, examine the dynamic patterns in unemployment between regions in Riau Province, and demonstrate the effect of government spending, investment, and natural resources on the unemployment rate. The method used is quantitative with static and dynamic panel data modelling. The data set used is the 2011-23 period and the district/municipality analysis unit. The results of the static panel model show two significant variables for reducing unemployment, namely FDI and manufacturing. For the dynamic model results, variables significantly reduce unemployment, including economic growth, FDI, natural resources, and the industrial sector, while government spending is positive for unemployment. The results of this study prove the occurrence of a dynamic pattern in unemployment, so severe handling is needed from policymakers for the long term.